Implementasi Pengabdian Bimbingan dan Konseling Islam (BKI) IAI Darussalam Blokagung pada Program "Bengkel Sakinah" untuk Perlindungan Perempuan dan Anak di Banyuwangi - Musafiri, M. Rizqon Al; Hafifah, Nur; Sa'diyah, Halimatus; Obianto, Agung (Proceedings of Annual Conference on Community Engagement, 2022)
The dynamics of problems in the family today are increasingly diverse, widespread, and unlimited. The family concept is no longer limited by an inclusive structure and division of roles but also requires the government's role in solving family problems. One effort that can be made is to maximize the role of posyandu in assisting families in need. Posyandu is a place for health care carried out from, by, and for the community under the guidance of the relevant officers. This service focuses on women and children in Banyuwangi Regency through the posyandu program in each hamlet. The purpose of this service is carried out by the Islamic Guidance and Counseling Study Program of IAI Darussalam Blokagung to provide consultations to women and children in Banyuwangi to help solve their problems. The strategy for implementing the "Sakinah Workshop" program is in collaboration with PKK Banyuwangi Regency, Posyandu Meja 6 in each hamlet, and Islamic Guidance and Counseling Study Program IAI Darussalam Blokagung Banyuwangi. The method used is to apply an assessment to clients who need it; after the assessment is given guidance services, the case is transferred to the relevant agency if it is not handled. The problems that have been resolved until the end of 2021 through this collaboration have handled 100 cases with cases that have been transferred to the Religious Courts with a total of 10 clients, the Banyuwangi Police with five clients, and the Social Service with five clients.